Information Practices and Digital Perspectives of Municipal Waste Recovery Providers in Europe - Luić, Ljerka; Labura, Krešimir (2021)
The priority of modern business systems of municipal waste management is recycling of waste materials while the imperative of their mission is determined by the degree of digital transformation which enables their reproduction, distribution, usage, and storage of information in digital form, as well as new ways of digital communication with the general public. In this paper the focus is on examining the information practices and digital perspectives of municipal waste recycling service providers in Europe. The goal of this paper was to detect information concepts relevant for establishing the degree of their digital maturity. Five data classes were created for the purpose of content analysis method to conduct research on practices on digital communication channels in seven countries to evaluate their availability and accuracy. The designed information model defines a unique conceptual framework of the digital communication information set of the municipal waste recycling service providers.
Bibliografija
Summary.